Enhancing Digital Competence of Vocational School Teachers Through Website-Based Learning Management System (LMS) - Latifah, Ana; Hudallah, Noor; Sutopo, Yeri; Anis, Samsudin (Universitas Negeri Semarang, 2025)
The digital competence of teachers is a crucial aspect in supporting the success of technology-based learning implementation. However, at SMK Merdeka Ulujami, issues were found regarding the low use of effective digital media in the learning process, mainly due to limited training and the lack of integrated media. This study aims to develop a website-based Learning Management System (LMS) as a solution to improve the digital competence of teachers. This research is a type of R&D with the development model being ADDIE. The LMS was developed using the WordPress platform and the Tutor LMS plugin, designed to support blended learning. The research was conducted at SMK Merdeka Ulujami with a total of 20 teachers as participants. Normality testing was conducted using the Shapiro-Wilk method, which showed normal results. Data analysis used paired sample t-tests and Normalized Gain. The results showed a significant improvement in the digital competence of teachers after using the LMS, with a Normalized Gain score of 0.93 or 93%, which is categorized as effective. Observations and interviews indicated that the LMS helped teachers manage digital classrooms efficiently and in a structured manner. However, challenges remain, especially with older teachers who are less familiar with software, highlighting the need for continuous support.